(untitled) (Research, Society and Development, 2021)
The partial replacement of cement by mineral additions such as metakaolin has been widely applied in the production of high-strength and durable concretes due to the pozzolanic action, allowing a reduction in the consumption of cement. Tests are performed to determine the mechanical properties of these materials, such as compressive strength, for which there are different levelling techniques of specimens, such as sulphur and neoprene, indicated for different resistance classes. The present study aimed to characterize the behaviour, in the hardened state, of concrete produced with high initial strength Portland cement (CPV-ARI) and metakaolin and evaluate the different levelling methods. Three groups of samples dosed by the IPT-EPUSP method, with mix designs of 1:3, 1:5, and 1:6, and replacements of 8 and 10% of cement by metakaolin, were subjected to compressive strength test, at the ages of 28 days, with levelling by neoprene, and 90 days, with levelling by sulphur. It was observed an increase in strength with addition of metakaolin at both ages. Comparing the results in the two ages, it was verified an increase in strength for the mix designs 1:5 and 1:6 and a reduction for the mix design 1:3. Such fact can be explained by the high strengths achieved by this mix design. As the levelling method used was sulphur, it is confirmed the imprecision of results for strengths above 50 MPa with this technique.